Detection of non-communicable diseases among adolescents as an effort to enhance community participation - Romdzati Romdzati; Erfin Firmawati; Dyah Dwi Astuti; Fiona Meylawati (Universitas Muhammadiyah Magelang, 2024)
Non-communicable diseases (NCDs) are a global health threat, causing high morbidity and mortality rates worldwide, including in Indonesia. The Special Region of Yogyakarta ranks second nationally in the prevalence of NCDs. One of the preventive and control measures for NCDs is through Integrated NCD Posts (Posbindu PTM), targeting individuals aged 15 to 49 years. Recognizing the importance of involving adolescents in NCD prevention and control, this community service program aims to provide education and training for adolescents on NCDs and risk factor detection. The activities were conducted using lecture and roleplay methods, involving 12 adolescents as active participants. Participants were given an understanding of the functions and importance of Posbindu PTM, as well as strategies for preventing and controlling NCDs. During the training, participants took turns practicing as Posbindu PTM cadres, performing duties according to procedures at stations one through five. Evaluation results indicated a significant increase in participants' knowledge, with the average score improving from 71.6 to 87.5. It is expected that adolescents' involvement in this program can strengthen early detection and control efforts for NCD risk factors.